This handy Spectrum Math Grade 4 Answer Key Chapter 6 Lesson 6.4 Adding Fractions with Like Denominators provides detailed answers for the workbook questions.
Spectrum Math Grade 4 Chapter 6 Lesson 6.4 Adding Fractions with Like Denominators Answers Key
Add the numerators.
\(\frac{2}{8}\) + \(\frac{5}{8}\) = \(\frac{2+5}{8}\) = \(\frac{7}{8}\)
Write the sum over the common denominator.
Add.
Question 1.
a. \(\frac{3}{12}\) + \(\frac{8}{12}\) = ______________
Answer:
\(\frac{11}{12}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{12}\) + \(\frac{8}{12}\) = \(\frac{3+8}{12}\) = \(\frac{11}{12}\)
Write the sum over the common denominator as shown above.
b. \(\frac{2}{5}\) + \(\frac{1}{5}\) = ______________
Answer:
\(\frac{3}{5}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{2}{5}\) + \(\frac{1}{5}\) = \(\frac{2+1}{5}\) = \(\frac{3}{5}\)
Write the sum over the common denominator as shown above.
c. \(\frac{3}{6}\) + \(\frac{2}{6}\) = ______________
Answer:
\(\frac{5}{6}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{6}\) + \(\frac{2}{6}\) = \(\frac{3+2}{6}\) = \(\frac{5}{6}\)
Write the sum over the common denominator as shown above.
d. \(\frac{1}{4}\) + \(\frac{2}{4}\) = ______________
Answer:
\(\frac{3}{4}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{4}\) + \(\frac{2}{4}\) = \(\frac{1+2}{4}\) = \(\frac{3}{4}\)
Write the sum over the common denominator as shown above.
Question 2.
a. \(\frac{1}{10}\) + \(\frac{3}{10}\) = ______________
Answer:
\(\frac{4}{10}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{10}\) + \(\frac{3}{10}\) = \(\frac{1+3}{10}\) = \(\frac{4}{10}\)
Write the sum over the common denominator as shown above.
b. \(\frac{3}{8}\) + \(\frac{2}{8}\) = ______________
Answer:
\(\frac{5}{8}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{8}\) + \(\frac{2}{8}\) = \(\frac{3+2}{8}\) = \(\frac{5}{8}\)
Write the sum over the common denominator as shown above.
c. \(\frac{1}{3}\) + \(\frac{1}{3}\) = ______________
Answer:
\(\frac{2}{3}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{3}\) + \(\frac{1}{3}\) = \(\frac{1+1}{3}\) = \(\frac{2}{3}\)
Write the sum over the common denominator as shown above.
d. \(\frac{2}{7}\) + \(\frac{2}{7}\) = ______________
Answer:
\(\frac{4}{7}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{2}{7}\) + \(\frac{2}{7}\) = \(\frac{2+2}{7}\) = \(\frac{4}{7}\)
Write the sum over the common denominator as shown above.
Question 3.
a. \(\frac{3}{5}\) + \(\frac{1}{5}\) = ______________
Answer:
\(\frac{4}{5}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{5}\) + \(\frac{1}{5}\) = \(\frac{3+1}{5}\) = \(\frac{4}{5}\)
Write the sum over the common denominator as shown above.
b. \(\frac{4}{12}\) + \(\frac{5}{12}\) = ______________
Answer:
\(\frac{9}{12}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{4}{12}\) + \(\frac{5}{12}\) = \(\frac{4+5}{12}\) = \(\frac{9}{12}\)
Write the sum over the common denominator as shown above.
c. \(\frac{3}{10}\) + \(\frac{6}{10}\) = ______________
Answer:
\(\frac{9}{10}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{10}\) + \(\frac{6}{10}\) = \(\frac{3+6}{10}\) = \(\frac{9}{10}\)
Write the sum over the common denominator as shown above.
d. \(\frac{2}{5}\) + \(\frac{2}{5}\) = ______________
Answer:
\(\frac{4}{5}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{2}{5}\) + \(\frac{2}{5}\) = \(\frac{2+2}{5}\) = \(\frac{4}{5}\)
Write the sum over the common denominator as shown above.
Question 4.
a.
Answer:
\(\frac{5}{8}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{8}\) + \(\frac{2}{8}\) = \(\frac{3+2}{8}\) = \(\frac{5}{8}\)
Write the sum over the common denominator as shown above.
b.
Answer:
\(\frac{7}{12}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{12}\) + \(\frac{4}{12}\) = \(\frac{3+4}{12}\) = \(\frac{7}{12}\)
Write the sum over the common denominator as shown above.
c.
Answer:
\(\frac{2}{6}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{6}\) + \(\frac{1}{6}\) = \(\frac{1+1}{6}\) = \(\frac{2}{6}\)
Write the sum over the common denominator as shown above.
d.
Answer:
\(\frac{3}{6}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{2}{6}\) + \(\frac{1}{6}\) = \(\frac{2+1}{6}\) = \(\frac{3}{6}\)
Write the sum over the common denominator as shown above.
e.
Answer:
\(\frac{2}{8}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{8}\) + \(\frac{1}{8}\) = \(\frac{1+1}{8}\) = \(\frac{2}{8}\)
Write the sum over the common denominator as shown above.
Question 5.
a.
Answer:
\(\frac{5}{8}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{8}\) + \(\frac{2}{8}\) = \(\frac{3+2}{8}\) = \(\frac{5}{8}\)
Write the sum over the common denominator as shown above.
b.
Answer:
\(\frac{7}{7}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{7}\) + \(\frac{4}{7}\) = \(\frac{3+4}{7}\) = \(\frac{7}{7}\)
Write the sum over the common denominator as shown above.
c.
Answer:
\(\frac{9}{10}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{7}{10}\) + \(\frac{2}{10}\) = \(\frac{7+2}{10}\) = \(\frac{9}{10}\)
Write the sum over the common denominator as shown above.
d.
Answer:
\(\frac{4}{5}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{5}\) + \(\frac{1}{5}\) = \(\frac{3+1}{5}\) = \(\frac{4}{5}\)
Write the sum over the common denominator as shown above.
e.
Answer:
\(\frac{11}{12}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{8}{12}\) + \(\frac{3}{12}\) = \(\frac{8+3}{12}\) = \(\frac{11}{12}\)
Write the sum over the common denominator as shown above.
Question 6.
a.
Answer:
\(\frac{8}{11}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{5}{11}\) + \(\frac{3}{11}\) = \(\frac{5+3}{12}\) = \(\frac{8}{11}\)
Write the sum over the common denominator as shown above.
b.
Answer:
\(\frac{2}{4}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{4}\) + \(\frac{1}{4}\) = \(\frac{1+1}{4}\) = \(\frac{2}{4}\)
Write the sum over the common denominator as shown above.
c.
Answer:
\(\frac{2}{2}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{1}{2}\) + \(\frac{1}{2}\) = \(\frac{1+1}{2}\) = \(\frac{2}{2}\)
Write the sum over the common denominator as shown above.
d.
Answer:
\(\frac{6}{7}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{5}{7}\) + \(\frac{1}{7}\) = \(\frac{5+1}{7}\) = \(\frac{6}{7}\)
Write the sum over the common denominator as shown above.
e.
Answer:
\(\frac{4}{9}\)
Explanation:
When the denominators are same, then add the numerators.
\(\frac{3}{9}\) + \(\frac{1}{9}\) = \(\frac{3+1}{9}\) = \(\frac{4}{9}\)
Write the sum over the common denominator as shown above.